End-of-Life Delirium: Issues Regarding Recognition, Optimal Management, and the Role of Sedation in the Dying Phase - Bush, Shirley H.; Leonard, Maeve M.; Agar, Meera; Spiller, Juliet A.; Hosie, Annmarie; Wright, David Kenneth; Meagher, David J.; Currow, David C.; Bruera, Eduardo; Lawlor, Peter G. (Journal of pain and symptom management, 2014)
In end-of-life care, delirium is often not recognized and poses unique management challenges, especially in the case of refractory delirium in the terminal phase. To review delirium in the terminal phase context, specifically in relation to recognition issues; the decision-making processes and management strategies regarding its reversibility; the potential refractoriness of delirium to symptomatic treatment; and the role of sedation in refractory delirium. We combined multidisciplinary input from delirium researchers and knowledge users at an international delirium study planning meeting and relevant electronic database literature searches (Ovid Medline, Embase, PsycINFO, and CINAHL) to inform this narrative review. The overall management strategy for delirium at the end of life is directed by the patient's prognosis in association with the patient's goals of care. As symptoms of delirium are often refractory in the terminal phase, especially in the case of agitated delirium, the judicious use of palliative sedation is frequently required. However, there remains a lack of high-level evidence for the management of delirium in the terminal phase, including the role of antipsychotics and optimal sedation strategies. For the family and health-care staff, clear communication, education, and emotional support are vital components to assist with decision making and direct the treatment care plan. Further research on the effectiveness of delirium management strategies in the terminal phase for patients and their families is required. Further validation of assessment tools for diagnostic screening and severity measurement is needed in this patient population.